Use of acoustic refuges by freshwater fish: Theoretical framework and empirical data in a three‐species trophic system. (14th February 2018) - Roca, Irene T.; Magnan, Pierre; Proulx, Raphaël
Abstract: Sounds are more easily transmitted underwater than through air and many freshwater fish species can hear them, particularly over the low frequencies. Recent studies on freshwater fish evidenced that hearing sensitivities can be limited by the level of ambient noise, a phenomenon also known as acoustic masking. However, it is still unclear whether variations in ambient noises, such as those produced by human activities, may alter fish trophic interactions. The general objective of this study was to propose and evaluate a theoretical framework explicitly linking fish attack rates to species hearing sensitivities and ambient noise levels in freshwater ecosystems. The proposed model shows that the feeding activity of fish at an intermediate position in the food web is conditional on the probability of being acoustically detected by their predators, or of encountering an acoustically distressed resource. Model simulations and preliminary field results suggest that yellow perch ( Perca flavescens ) could feed more actively in the presence of augmented ambient noise levels. Yellow perch captures per unit effort were higher by a factor of 2.7 in noisy versus quiet days. We argue that fish exposed to intermediate levels of noise could maximise the probability of detecting food patches while minimising their predation risk. Acoustic monitoring programmes for freshwater ecosystems require a fundamental knowledge of underwater noise levels, species hearing sensitivities and features affecting sound propagation. The approach proposed in this paper is seminal in linking the above descriptors in a coherent mathematical framework to understand the effect of underwater sounds on trophic interactions. Such framework is needed to make testable predictions and generalise to other taxa and ecological contexts.